Critical Co-Design and Agency of the Real. (2nd September 2021) - Hernandez Ibinarriaga, Desiree; Martin, Brian
Abstract: This article explores research that was undertaken in a PhD project that investigated the creation and effectiveness of Critical Co-Design as a methodology. In particular, it explores how this methodology enabled successful outcomes from a workshop that was conducted with young Indigenous Australian women. The methodology and workshop aimed to create a platform for the researcher to work alongside Indigenous peoples in Australia in order to create mutually beneficial ways of working. Here, the authors reflect upon this research and postulate the importance of privileging Indigenous ways of knowing as a way of shifting approaches to design thinking. By examining the interconnectedness between these Indigenous ways of knowing and design thinking epistemology, the authors offer a paradigm for design thinking that engages the politics and the broader promise of (de)coloniality. This article reconfigures how design scholars and creative practitioners ascribe value to Indigeneity and practice by positioning Indigenous ontologies at the forefront of design thinking in general.